Health Behavior Models and Mental Health Literacy in Realizing Family Resilience - Sumi Lestari; Khoirul Anam (Jurnal Pendidikan Progresif, 2024)
Health Behavior Models and Mental Health Literacy in Realizing Family Resilience. Objektive: The family is the most important unit in forming health behavior to create a resilient family that is happy and prosperous as the basic foundation for the integrity of strength and sustainable development, thus the family is the heart of an individual's life. To live a life, the main key is physical and mental health, if the condition of the body and soul is healthy, then individual activities and activities will run smoothly and in accordance with expectations. The aim of this research is to obtain a fit model between mental health literacy and health behavior to increase family resilience. In addition, it examines the relationship between mental health literacy and health behavior to increase family resilience. Method: The method in this research is quantitative by conducting model tests using Structural Equation Modeling (SEM). The subjects in this research were 125 married families, men and women throughout Indonesia. The measuring instrument used is the health belief model scale for exercise (HBMS-E), while mental health literacy uses the Mental Health Literacy Questionnaire- for adults (MHLq-fA) and family resilience uses the family functioning style scale measuring instrument. (FFSS). Finding: The research results show a relationship between mental health literacy and health behavior to increase family resilience. BesidesThe modified model obtained shows that there is no difference between the model and the data. So the model is theorized fit with data. Conclusion: The model is theorized fit with data. Keywords: mental health literacy, family resilience and health behavior.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202462